Dampak Gadget Terhadap Perkembangan Fungsi Sosial Remaja Di Pertanian IV Lebak Bulus Jakarta Selatan - Muhammad Rifki; Moh. Amin Tohari (Journal Innovation In Education, 2023)
Teenagers whose daily lives are altered by excessive gadget use may face a variety of health and social issues as a result of their overindulgence in technology. The purpose of this study is to ascertain how teenage social function development is impacted by gadget use. This study employs descriptive approaches in a qualitative manner. Data were gathered by documenting, interviewing, and observation. Purposive sampling is the method used in this study to select informants. Additionally, this study triangulates its data in order to verify the information derived from the field findings.The study's findings show what adolescents go through in terms of social functions, including developing new, more mature relationships with both male and female peers, achieving male and female social roles, accepting and making use of their physical condition, seeking emotional independence from parents and other adults, achieving guaranteed economic freedom, making career and family-planning decisions, and developing intellectual concepts and skills that are critical for civic competence. Additionally, informants reported negative effects, such as excessive use of gadgets that waste money on everyday necessities and negatively impact teenage behavior.